SHALL YOU BE 'UNMARRIED' TO GET A JOB IN INDONESIA? CRITICAL DISCOURSE ANALYSIS OF JOB RECRUITMENT PROCESS IN INDONESIA - Pratama, Hendi (PRASASTI: Journal of Linguistics, 2016)
In this article, I look into four job vacancy advertisements published by two state owned enterprise and two private companies. Using critical discourse analysis (CDA), this article focuses on the text implicit discrimination shown in the usage of the term "unmarried" or the synonyms which are often shown in the text for job vacancy in Indonesia. In order to keep the validity of the data, the job vacancy ads were taken directly from the companies’ websites. This study uses Fairclough (1995) framework on the technologization of the discourse. There are three arguments to be proven in this paper: (1) advertisers’ ideology supporting the discrimination of marital status, (2) advertisers’ perception toward societies’ ignorance in the ideology, and (3) to show the existence of anti-mainstream ideology similar to technologization of discourse.    Keywords: critical discourse analysis, discrimination, ideology